Pengaruh Bauran Pemasaran terhadap Pemilihan Destinasi Taman Wisata Mekarsari - Rini Fransiska; Julita (Journal of Tourism Destination and Attraction, 2013)
The number of tourists to Bogor has been increasing in recent years. Competition among tourists’ destinations within the region cannot be avoided. To face the great competition, tourism destination requires a good marketing mix to attract tourists. This study, conducted in Taman Wisata Mekarsari, aims to investigate the impact of marketing mix on destination choice by travelers to Mekarsari. Researchers used the 7P's of marketing mix as the independent variable (pull factors) consisting product, price, place, promotion, people, process and physical evidence and 2 push factors, i.e. socio-demography and motivation. The dependent variable is the destination choice by tourists to visit Mekarsari. By using convenience sampling technique, 100 respondents were sampled in this study. Multiple regression analysis was performed to determine whether the marketing mix components influence the destination choice. The results show that the marketing mix component simultaneously affects the destination choice to Mekarsari. Product, process, physical evidence and promotion have a significant influence on the destination choice, while the remaining price, place and people do not have a significant influence. Among the socio-demographic factors only gender and occupation have discriminant function on the destination choice, whereas for the motivational factors only education motivation show discriminant function on the destination choice Taman Wisata Mekarsari. This study recommends the management of Taman Wisata Mekarsari to optimize products, promotion, process and physical evidence in an effort to increase the number of visits.